Conservation strategy of a nature reserve in Mediterranean ecosystems: the effects of protection from grazing on biodiversity - Verdú, J. R.; Crespo, M. B.; Galante, Eduardo (Biodiversity and Conservation, 2000)
Protection of natural areas has caused the elimination of traditional grazing activity on many occasions. As a result, in Mediterranean ecosystems a loss of biodiversity is usually related to a decrease of grassland and grassland–bush mosaic areas. In order to establish relationships between land use and the relative importance of each type of habitat in terms of species richness and endemicity, the Font Roja Natural Park in Alicante Province (SE Iberian Peninsula) was studied. Four sites were selected representing the four different existing habitats: a wooded area (holm-oak forest), a dense shrubland, a dense grassland, and a grassland–shrubland mosaic area. In each site, the species composition of vegetation and dung beetle fauna were analysed. The results showed that the highest diversity and endemicity, for plants and beetles, were concentrated in the dense grasslands and the grassland–shrubland mosaic. Thus, controlled grazing activity of sheep and goats which maintained a diverse variegated landscape would favour the historical sustenance of the biodiversity of Mediterranean ecosystems, as that would allow a remarkable diversity of habitats with higher conservation levels of existing species richness and endemicity. Therefore, we propose a reintroduction of traditional grazing of sheep and goats throughout ecological, cultural and economical measures, which would include guidelines and regulations, set out to boost an integrated rural policy.
Keywords: dung beetles; endemicity; impact; management; vascular plants